Competitive Strategy Of Wholesalers Using Digital Business In Banjarmasin - Novia Nour Halisa; Dessy Maulina; Dita Anggraini; Rika Nur Asyifa; Sherly Saputri (Hut Publication Business and Management, 2023)
This study aims to analyze the development of digital technology in supporting businesses run by traders and analyze strategies that can be developed to increase the competitiveness of Wholesale Market traders in Banjarmasin City. The method used in this research is qualitative research with a survey approach ie do field research ( field research ) on wholesale market traders in the city of Banjarmasin. Informants selected in this study were the Head of the Department of Trade and Industry of the City of Banjarmasin, traders and business people at the Banjarmasin Wholesale Market. Research results explain part Most traders in the Sudimampir market have implemented digital business. Apart from that there is Online business can attract more consumers not only within the city but also outside the region as well promote online with flexible time and profitable for traders. Furthermore The use of social media as a means of promotion by merchants cannot be separated from the marketing strategy, namely advertising, marketing through e-commerce, and promotions price . Keywords: Digital Business, Wholesale market